STANDARDIZATION AND COMPARATIVE ANALYSIS OF DIFFERENT MARKETED FORMULATION OF AGNIMUKH CHURNA - Sharath M.V.; S.M. Prasanna; G. Narayana Murthy; M.C Ravi (Journal of Biomedical and Pharmaceutical Research, 2020)
The subject of herbal drug standardization is massively wide and deep, there is so much to know and so much seemingly contradictory theories on the subject of herbal medicine and its relationship with human physiology and mental function. India needs to explore the important formulations in the classical ayurvedic texts. This can be achieved only if the herbal products are evaluated and analysed using sophisticated modern techniques of standardization such as UV-Visible, TLC, HPLC, HPTLC, etc. The present paper reports on Standardization and Comparative Analysis of Different Marketed Formulation of Agnimukh Churna, a poly herbal ayurvedic medicine used in treatment of anorexia, indigestion, constipation, spleen disorders, non bleeding hemorrhoids’ and abdominal pain.Agnimukh Churna was prepared as per Ayurvedic text of Yogaratnakara, India. In-house preparation and two marketed have been standardized on the basis of organoleptic characters, physical characteristics, physico-chemical properties, TLC and HPLC for the estimation of marker compound Piperine. The set parameters were found to be sufficient to evaluate the Churna and can be used as reference standards for the quality control/quality assurance laboratory of a Pharmaceutical house.Keywords: Agnimukh Churna; Physicochemical parameters; organoleptic characters; Polyherbal formulation; Standardization; Piperine